Le community manager à l’épreuve de la capitalisation des connaissances et des mémoires techniques - Bruno Chaudet (Communiquer)
The role of community manager in organizations is not just about managing reputations and brands. Their role can also include formatting a socio-technical environment that allows employees to carry out their work. Here we will discuss the topic of community management in terms of internal communication, or managerial. We’ll specifically examine the hypothesis that community manager participates in organizational knowledge capitalization process. Organizational knowledge is distributed in socio-technical systems. So, we’ll discuss the concept of technical memory to see how technical objects participate in capitalization of knowledge and therefore the community management practices.